PTU-020 Diagnosing small bowel crohn's disease – using capsule when the imaging is negative. (22nd June 2015) - Coombs, A; Chelvaratnam, U; Terlevich, A; Marden, P
Abstract : Introduction: The European Crohn's and Colitis Organisation guidelines 1 state that small bowel capsule endoscopy (SBCE) should be reserved for patients in whom the clinical suspicion for Crohn's disease remains high despite negative evaluations with ileocolonoscopy and radiological examinations. SBCE has been shown to detect a higher yield of non-stricturing small bowel Crohn's disease compared to CT and small bowel barium radiology 2 and improved detection rates compared with MRI. 3 Southmead Hospital is a tertiary referral centre for SBCE which receives referrals throughout the Somerset region. We assessed the diagnostic yield from patients referred for CE for suspected Crohn's Disease. Method: All patients referred for SBCE to assess for small bowel Crohn's disease between May 2013 and May 2014 were identified. Patients with known Crohn's disease or positive findings on small bowel imaging were excluded. Patient demographics and CE findings were collected from patient notes, electronic results or referral information. CE videos were interpreted by one of three gastroenterology consultants experienced in interpreting SBCE video. Results: 61 patients were referred for SBCE following negative small bowel imaging of which 14 (22.9%) patients had positive findings on SBCE. 9 (64.3%) were female (age range of 17–66 years; mean 42 years). 1 patient (7.1%) had pathology in the proximal SB, 2 (14.3%) in the mid SB, 6 (42.3%) in the distal SB whilst 6 (42.3%) had pathology throughout the SB. Prior to SBCE, 5 patients (35.7%) had negative small bowel MRI, 2 (14.3%) had negative CT abdomen, 5 had (35.7%) negative small bowel enema and 2 (14.3%) had both negative MRI and CT abdomen. Conclusion: SBCE diagnosed Crohn's disease in 22.9% of patients that was not detectable on small bowel imaging. In our experience, SBCE is a worthwhile investigation in patients in whom there is a high clinical suspicion of Crohn's disease with previous negative imaging including small bowel MRI. Disclosure of interest: None Declared. References: Van Assche G, Dignass A, Panes J, Beaugerie L, Karagiannis J, Allez M, Stange E. The second European evidence-based consensus on the diagnosis and management of Crohn's disease: definitions and diagnosis. J Crohns Colitis 2010;4(1):7–27 Triester SL, Leighton JA, Leontiadis GI, Gurudu SR, Fleischer DE, Hara AK, Sharma VK. A meta-analysis of the yield of capsule endoscopy compared to other diagnostic modalities in patients with non-stricturing small bowel Crohn's disease. Am J Gastroenterol. 2006;101(5):954–964 Gölder SK, Schreyer AG, Endlicher E, Feuerbach S, Schölmerich J, Kullmann F, Herfarth H. Comparison of capsule endoscopy and magnetic resonance (MR) enteroclysis in suspected small bowel disease. Int J Colorectal Dis. 2006;21(2):97–104